2013
DOI: 10.1002/chem.201301411
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Metalloporphyrins in a Self‐Assembled Cubic M8L6 Cage: A New Molecular Flask for Cobalt–Porphyrin‐Catalysed Radical‐Type Reactions

Abstract: The synthesis of a new, cubic M8L6 cage is described. This new assembly was characterised by using NMR spectroscopy, DOSY, TGA, MS, and molecular modelling techniques. Interestingly, the enlarged cavity size of this new supramolecular assembly allows the selective encapsulation of tetra(4-pyridyl)metalloporphyrins (M(II)(TPyP), M = Zn, Co). The obtained encapsulated cobalt-porphyrin embedded in the cubic zinc-porphyrin assembly is the first example of a catalytically active encapsulated transition-metal comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
66
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(69 citation statements)
references
References 62 publications
3
66
0
Order By: Relevance
“…Earlier reports, using different diazo substrates, showed that catalytic substrate activation took place inside the cavity of these type of molecular flasks, thus leading to different selectivities compared to similar but non-encapsulated catalysts. [3] In good agreement, the results described in this paper show that allows size-selective substrate transformations. This is most easily explained by a slower migration of larger substrates through the pores of the cage compared to smaller substrates (Figure 2).…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Earlier reports, using different diazo substrates, showed that catalytic substrate activation took place inside the cavity of these type of molecular flasks, thus leading to different selectivities compared to similar but non-encapsulated catalysts. [3] In good agreement, the results described in this paper show that allows size-selective substrate transformations. This is most easily explained by a slower migration of larger substrates through the pores of the cage compared to smaller substrates (Figure 2).…”
supporting
confidence: 85%
“…Recently, we have reported the synthesis of the Nitschke-type M 8 L 6 cubic cage 1 through self-assembly (Scheme 1). [2,3] Furthermore, we showed that 1 is suitable to encapsulate tetra(4-pyridyl)metalloporphyrins (M(TPyP) (2) with M = Zn, Co) to give the M 8 L 6 P 1 cubic cages and (P= porphyrin guest). In particular, the encapsulation of a cobalt-porphyrin is interesting, because these complexes are known for their catalytic activity in radical-type reactions.…”
mentioning
confidence: 99%
“…Interestingly, many catalytic reactions operate through ad inuclear mechanism [7] or deactivate via ad inuclearp athway; [8,9] by encapsulation of at ransition metal complex, such decomposition pathways can be suppressed, leading to higher catalytic turnover numbers. [10] In principle, an encapsulatione ventc ould also change the catalyticp athway of ar eaction, and as such can be used as as witch for ac atalytict ransformation. Switchable catalysis is an interesting upcoming field of research as it provides new tools to control the reaction process with externals timuli such as light, pH, or metalc oordination, ac onceptt hat is important to control reactions in nature.…”
mentioning
confidence: 99%
“…26 As a result, large architectures capable of binding small substrates are rare. Closing off the interior void with bulky organic units, 27,28 using rigid ligands with cavity-directed substituents, 29 or exploiting unsaturated metal coordination sites, 30 are useful means of enforcing the binding of guests into discrete spaces. 31 However, these methods rely on pre-programmed features within the assembly.…”
mentioning
confidence: 99%